2008
DOI: 10.1038/ijo.2008.181
|View full text |Cite
|
Sign up to set email alerts
|

Food and nutrient intake, nutritional knowledge and diet-related attitudes in European adolescents

Abstract: Background and objective:To provide an overview of methods used to assess food and nutrient intake, nutritional knowledge and diet-related attitudes in the Healthy Lifestyle in Europe by Nutrition in Adolescence Cross-Sectional Study (HELENA-CSS), with selected results from the feasibility study. Material and Methods: To assess food intake in 13-to 16-year-old adolescents, a previously developed computer-assisted and self-administered 24-h recall was adapted for international use. Food consumption data were li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 40 publications
10
35
2
4
Order By: Relevance
“…Similar accounts were found in the literature on the lack of association between awareness and levels of physical activity, age, socioeconomic status, gender 16,25,28 and BMI, 28,30 except for the Italian study 27 which showed a slightly higher awareness score (1 point total score) in healthy subjects compared to overweight ones (p < 0.003). Studies are consistent on the grounds that food consciousness is related to environmental and family factors, besides state of motivation itself, and not to organic factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar accounts were found in the literature on the lack of association between awareness and levels of physical activity, age, socioeconomic status, gender 16,25,28 and BMI, 28,30 except for the Italian study 27 which showed a slightly higher awareness score (1 point total score) in healthy subjects compared to overweight ones (p < 0.003). Studies are consistent on the grounds that food consciousness is related to environmental and family factors, besides state of motivation itself, and not to organic factors.…”
Section: Discussionsupporting
confidence: 87%
“…In Europe, the HELENA study 28 has found percentages ranging 50-70% for adequate nutritional awareness among adolescents aged 13-16. These studies, however, do not discriminate specifi c data related to FV awareness.…”
Section: Discussionmentioning
confidence: 99%
“…41 To assess eating behaviour, a validated eating inventory questionnaire was adapted for the study, as described. 42,43 Briefly, the Eating Behaviour and Weight Problems Inventory for Children (EWI-C) includes 60 items on 10 subscales measuring (1) hunger level and susceptibility to food cues, (2) importance and impact of eating on sense of well-being, (3) eating as a means of coping with emotional stress, (4) concerns about eating and weight, (5) dietary restraint, (6) attitude towards healthful nutrition, (7) attitude towards the obese, (8) pressures to eat from parents, (9) fear of weight gain and (10) figure dissatisfaction. To determine attitudes regarding food choices, a purpose-built food choices and preferences questionnaire was used, which includes three sections: (1) opinions about food choices, preferences, diet and health, (2) choices and preferences of snack foods and drinks and (3) important influences on food choices and preferences.…”
Section: Study Subjectsmentioning
confidence: 99%
“…13 Microsoft Visual Basic6.0 was used to develop the program, which implies that the current version is a desktop version.…”
Section: Instrumentmentioning
confidence: 99%